Design and fabrication an electric buggy frame - Mohd Yazid, S Hamid (2007)
Due to the large area of University Malaysia of Pahang factories especially the factory of Faculty of Mechanical Engineering, a problem arises that it takes quite a lot one's energy and time to move around the compound and also to carry or transporting small to medium-sized things that can be carried by a person. To encounter this problem, a small buggy frame will be build. This frame will acts as a foundation to the buggy that will be build for the purpose of carrying burden and load within the compound of University Malaysia Pahang factory. The buggy will be design to transport 2 persons in one time. In this project, there are three stages of development will be done which are designing the electric buggy frame by using CAD software, analyzing the stress distribution on the frame when the load is applied and fabricating the frame.